Global Industrial Production Chains in Latin America From A Structuralist Perspective - Lauxmann, Carolina Teresita; Trevignani, Manuel; Fernández, Víctor Ramiro (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Recovering the main concepts of Latin American structuralism, this article examines the potentialities and limitations regarding the new development paradigm, the Global Value Chain approach, which over the last two decades has had an important influence among academic community and within international organizations. To achieve this, the authors analyze the exacerbation of the peripheral condition of the Latin American productive structures associated with their insertion in global production, contrasting them with the successful experiences of structural transformation of the East Asian countries. From the analysis, the authors draw some elements to rethink the importance of industrialization for development, and the policies needed to promote it in the current scenario of global production chains.